Determination of optimal prey for rearing tropical gar Atractosteus tropicus (Lepisosteiformes: Lepisosteidae) - Escalera-Vázquez, Luis H. (2018)
Larval feeding studies of both ornamental and consumable fish species are important for formulating successful management, and culture strategies for conservation purposes. In the present study, we evaluated prey selectivity for the tropical gar Atractosteus tropicus in the larval stage (first 8 weeks) using the zooplankton Artemia fransiscana, Daphnia pulex and Moina macrocopa as prey following the hypothesis that prey selection of the fish species is related not only to prey species preferences but to the difference in prey densities present in the environment. Functional responses were tested at prey densities of 0.2, 0.5, 1.0, 2.0, 4.0 and 8.0 ind. mL-1 and analyzed using Manly’s α. For prey selectivity, we used the three zooplankton species at three different densities. In these two experiments the fish larvae were allowed to feed for 45 min. To quantify feeding behavior (encounters, attacks, captures, ingestions, rejections) we used a density of 1 ind. mL-1 using each prey species based on 10 minutes of direct observation. Our results showed a functional response Type II for A. tropicus preying mostly on A. franciscana and M. macrocopa. The Manly’s α index showed that M. macrocopa and A. franciscana are the most preys selected. The values for encounters for the three prey species were relatively constant during the eight weeks. Encounter values for the cladocerans were low in comparison to A. franciscana; however, high success in capture and ingestion was observed for all prey species used. Our results from the functional response experiments supports the hypothesis that A. tropicus is an active predator presenting a functional response of a carnivorous fish and the shift in prey selection suggests that even at low prey availability, A. tropicus is able to manipulate and feed on zooplankton of wide range in size. Also, according to our results, we suggest the use of a mix of A. franciscana and M. macrocopa to feed A. tropicus in culture systems in concentrations ≈ 2 ind. mL-1 during the first 3 weeks of age and then shift to M. macrocopa from the 4 week. Our results, in conjunction with studies on the survivorship of the juveniles would aid in conservation efforts and improve the production of gars in aquaculture.